2021
DOI: 10.1111/jnc.15270
|View full text |Cite
|
Sign up to set email alerts
|

Collybistin SH3‐protein isoforms are expressed in the rat brain promoting gephyrin and GABA‐A receptor clustering at GABAergic synapses

Abstract: Collybistin (CB) is a guanine nucleotide exchange factor (GEF) selectively localized at GABAergic and glycinergic postsynapses. Analysis of mRNA shows that several isoforms of collybistin are expressed in the brain. Some of the isoforms have a SH3 domain (CBSH3+) and some have no SH3 domain (CBSH3−). The CBSH3+ mRNAs are predominantly expressed over CBSH3−. However, in an immunoblot study of mouse brain homogenates, only CBSH3+ protein isoforms were detected, proposing that CBSH3− protein might not be expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(188 reference statements)
1
3
0
Order By: Relevance
“…We did not observe any changes in density, MFI, or size of VGAT puncta, which is consistent with previous studies indicating that CB is not synaptogenic: knocking out CB in mice, while disruptive of gephyrin clusters in certain brain regions, does not affect presynaptic GABAergic innervation (Papadopoulos et al, 2007), nor does knockdown of CBSH3-or CBSH3+ isoforms (George et al, 2020) or overexpression of CB (Chiou et al, 2011;Fekete et al, 2017). Nevertheless, we observed a left-shift in interevent interval and increase in frequency of mIPSCs in CB2SH3-overexpressing cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We did not observe any changes in density, MFI, or size of VGAT puncta, which is consistent with previous studies indicating that CB is not synaptogenic: knocking out CB in mice, while disruptive of gephyrin clusters in certain brain regions, does not affect presynaptic GABAergic innervation (Papadopoulos et al, 2007), nor does knockdown of CBSH3-or CBSH3+ isoforms (George et al, 2020) or overexpression of CB (Chiou et al, 2011;Fekete et al, 2017). Nevertheless, we observed a left-shift in interevent interval and increase in frequency of mIPSCs in CB2SH3-overexpressing cells.…”
Section: Discussionsupporting
confidence: 92%
“…CB may be differentially expressed between various interneuron types. It has been shown that PV+ interneurons in the hippocampus and cerebral cortex contain higher levels of endogenous CB (Arhgef9) transcripts and protein than other interneurons (Paul et al, 2017;George et al, 2020). We found that transduction with the HACB2-AAV resulted in increased expression of CB in transduced interneurons compared to control EGFP-AAV transduced interneurons.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This downregulation was accompanied by the loss of functional GABAergic synapses (Groeneweg et al., 2018; Liang et al., 2014). Collybistin is a guanosine diphosphate‐guanosine triphosphate (GDP‐GTP) exchange factor encoded by the Rho‐guanine nucleotide exchange factor 9 gene (ArhGEF9) (George S et al., 2020; Yao et al., 2020), which is an important determinant of inhibitory postsynaptic membrane formation and plasticity. The absence of collybistin can reduce gephyrin and GABA A receptor clustering and impair spatial learning ability (Yao et al., 2020).…”
Section: Discussionmentioning
confidence: 99%